(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2019)
In contemporary multicultural Britain, the concept of social cohesion has been a pressing priority for not only politicians and sociologists but also for the various British ethnic minorities. Race riots like those of 2001 in Northern Britain and the events of 7/7 in London (2005) put into question the allegiances of different British ethnic populations. They equally shed light on the real or perceived lack of social and cultural communication between the established British host population and the British ethnic and immigrant communities. Hence, social cohesion came to the fore as the new jargon of governance in contemporary Britain.This article analyzes on the concept of social cohesion and its applicability within an officially declared multicultural community like that of Great Britain. The concept will be reviewed, defined and approached from different liberal political perspectives (Robert Dahl’s pluralist approach and Arend Lijphart’s consociationalism to the more recent Will Kymlicka’s group-differentiated citizenship) while paying special attention to the British context. Bhikhu Parekh’s conception of the different theoretical approaches to the issue of social cohesion that are pertinent to liberal capitalist societies in general and the British context, in particular, is investigated. The aim of this study is to highlight the complexity of the normative accounts of the political scientists regarding the challenges that face multicultural Britain in coming to terms with its endeavour of creating “unity within diversity”. The 2002 White Paper and security speech of David Cameron (2011) political discourses are analyzed and evaluated to decipher how they understood national identity in relation to cultural diversity and social cohesion.